2015
DOI: 10.1007/s00784-015-1572-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of vdr, cyp27b1, cyp24a1 and mthfr gene polymorphisms with oral lichen planus risk

Abstract: Identification of new molecular biomarkers could potentially contribute to determination of individuals with OLP predisposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 34 publications
0
22
7
Order By: Relevance
“…This might be explained by few numbers of patients in each subgroup analysis. These results were in contrary with Kujundzic et al 12 who reported no association between MTHFR genotype and OLP. This discrepancy could be explained by the difference between the studied populations, and the fact that Kujundzic et al 12 studied OLP patients, while in the current study cutaneous and oral lichen planus patients have been included in the analysis.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…This might be explained by few numbers of patients in each subgroup analysis. These results were in contrary with Kujundzic et al 12 who reported no association between MTHFR genotype and OLP. This discrepancy could be explained by the difference between the studied populations, and the fact that Kujundzic et al 12 studied OLP patients, while in the current study cutaneous and oral lichen planus patients have been included in the analysis.…”
Section: Discussioncontrasting
confidence: 94%
“…Kujundzic et al have studied the association between MTHFR gene polymorphisms and risk for OLP occurrence, but they did not report any significant association and also they did not assess this issue in CLP.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Information, such as demographic data, alcohol consumption habits and oral hygiene, were collected by one-to-one surveys using a questionnaire designed according to our research content. Prior to OLP diagnosis, participants who drank more than 20 alcoholic drinks per week were classified as heavy drinkers [9]. The periodontal status of all subjects including the gingival index (GI), periodontal index (PI) and bleeding on probing (BOP) was evaluated in both groups.…”
Section: Study Groups and Samplesmentioning
confidence: 99%
“…All SNPs were selected according to the following criteria: (1) minor allele frequency (MAF) ≥0.05 in the Chinese population and (2) a Hardy-Weinberg equilibrium test P-value ≥0.05. Tag SNPs were chosen to represent a set of variants with Abbreviation: OLP oral lichen planus strong linkage disequilibrium (LD) [9]. A total of eight SNPs in the VDR gene (rs731236, rs739837, rs757343, rs2107301, rs2239185, rs7975232, rs11574129 and rs11568820) were selected according to the above steps.…”
Section: Dna Isolation and Genotypingmentioning
confidence: 99%